Znaczenie praktyk pedagogicznych dla zmian w obszarze kluczowych kompetencji nauczyciela edukacji przedszkolnej i wczesnoszkolnej - Sikorska, Joanna; Schmidt, Anna (Studia Edukacyjne, 2018)
The future teacher, wanting to understand the child’s needs, his pursuit of self-realization and autonomy must build himself not only on theoretical knowledge, but also learn how to use this knowledge in educational practicum. In this context, preparing student teachers “through practicum for practicum” seems to be an extremely important element of their education, because only in this way will they be able to stimulate their own development, mature professionally, but also answer the question to what extent “being a teacher” is their true calling. Student teachers, especially those who have practicum in grades 1-3 of elementary school, pay more attention to the gradual departure in many institutions from the implementation of the concept of integrated education. The information obtained by them indicates that the “modifications”of the model of this education are largely caused by anxiety caused by low results achieved by children in tests aimed at checking the effectiveness of education. Undoubtedly, this is a cause for serious concern and remedial action, however, according to our research, many students are concerned that during lectures or even laboratories, run by some specialists realizing specificsubjects, they are only passive observers and have no opportunity to learn how to, in school conditions, complementarily combine tasks from many educational areas, in accordance with the assumptions of integral education. Thus, there is a significantdiscrepancy between the tasks carried out as part of classes at the university and pedagogical practicum.The authors of the article focus on both theoretical aspects of the issues raised and the results of their own research.